Multimodality in education 4.0: A case in an engineering context - Khoo, Linda Mei Sui; M.Subramaniam, Indra Devi; Feroz, Farah Shahnaz; Kanchymalay, Kasturi; Md Saad, Mohd Shamsuri (The World Academy of Research in Science and Engineering, 2020)
The emergence of Education 4.0 has enabled instructors to take advantage of multimedia resources, tools and interfaces in the teaching environment so as to prepare graduates for a global and digitalized work environment. This paper aims to investigate whether instruction based on the application of multimodality is effective in developing the oral communicative proficiency of learners with limited language proficiency in this Education 4.0 era and specifically in an engineering context. In this study, 15 students of limited language proficiency were immersed in multimodal enhanced classroom activities like creating video content, editing audio clips and other activities that facilitated meaning making. Classroom activities were designed and documented using The Learning by Design Model. The oral communicative proficiency levels of the learners were evaluated before and after 29 weeks of instruction using the Foreign Language Oral Skills Evaluation Matrix (FLOSEM). A Wilcoxon Signed-Ranks Test indicates a significant improvement in their proficiency levels despite numerous language inaccuracies. This study hence testifies that multimodality which advocates the affordances of media and modalities or a fusion of technologies to communicate knowledge is a step forward for future engineers to embrace Industry 4.0. Due to its effectiveness, this study calls for a design-oriented multimodal-based instruction in engineering institutions.